DOST-FNRI Center for Human Nutrition a collaborative and inclusive nutrigenomics research and development facility - Soliven, Samantha Beatrice O. (College of Architecture, University of the Philippines Diliman, 2019)
The Food and Nutrition Research Institute (FNRI) under the Department of Science and Technology (DOST) is the primary research arm of the Philippine government in terms of food and nutrition. With the advent of poor nutrition and non-communicable diseases in the country, FNRI is planning to expand their current 9 room Nutrigenomics laboratory to a full omics laboratory to further develop the study of nutrigenomics. This expansion to a satellite laboratory to further develop the study of nutrigenomics. This expansion to a satellite laboratory outside of Manila is called the Center for Human Nutrition, where this shall push for the usage of genomic tools to analyze nutrition and ultimately improve Filipino health. Since the study of nutrigenomics is new in the country, there are current and future expansion issues that the development shall tackle. These issues are ethical in terms of biobanking, the lack of collaboration between the different sectors and inclusivity. The research shall challenge the usual rigid and exclusive design of a laboratory and instead create a development wherein the spaces encourage users to interact and collaborate to ultimately close the gap between knowledge and implementation.